Community-Based Tuberculosis Prevention through Dayak Local Wisdom: A Qualitative Ethnographic Study - Tri Wahyuni; Cau Kim Jiu; Parliani Parliani (Journal of Applied Nursing and Health, 2026)
Background: Tuberculosis (TB) prevention in geographically remote indigenous communities may be constrained by cultural beliefs, stigma, limited access to health services, and locally embedded health practices. However, limited qualitative evidence has examined how Dayak local wisdom and customary structures can be integrated with community-based TB prevention in Bengkayang, Indonesia. This study aimed to explore community perceptions and practices related to TB and formulate a culturally grounded community-based TB prevention strategy integrating local wisdom with existing health services. Methods: A qualitative ethnographic study was conducted in selected Dayak communities in Bengkayang Regency, West Kalimantan, Indonesia. Forty-eight participants were recruited using purposive and snowball sampling, comprising Dayak traditional leaders (Temenggung), community health cadres, active and former TB patients, and members of the general community. Data were collected through in-depth interviews, focus group discussions, and participatory observation using interview guides, observation sheets, field notes, and audio recordings. Data were analyzed through data reduction, data display, and conclusion verification, with source and methodological triangulation used to enhance credibility. The study was reported in accordance with the Standards for Reporting Qualitative Research (SRQR). Results: Three major themes emerged. First, perceptions of TB reflected a transition from traditional interpretations and stigma toward biomedical understanding of TB as a treatable infectious disease. Second, local wisdom included social restriction practices, traditional herbal use as a complement to medical treatment, and customary norms discouraging indiscriminate spitting, which could be aligned with TB prevention principles. Third, community-based prevention was supported by collaboration among traditional leaders, health cadres, and health services. Traditional leaders served as culturally trusted actors for reducing stigma and supporting treatment adherence, while cadres facilitated community-level case finding and health education. Conclusion: Dayak local wisdom and customary social structures provide potentially valuable cultural resources for strengthening community-based TB prevention. Integrating traditional leaders and community health cadres with formal health services may improve the cultural acceptability of TB education, stigma reduction, case finding, and treatment support. Further research should evaluate the implementation and effectiveness of culturally grounded TB prevention strategies.